EFFECTIVENESS AND EFFICIENCY OF FINANCIAL MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDes) - Angraeni, Natila; Musmulyadi, Musmulyadi; Arwin, Arwin; Rusnaena, Rusnaena (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
This research aims to analyze the effectiveness and efficiency of financial management in the Village-Owned Enterprise (BUMDes)